PERLINDUNGAN HUKUM RAHASIA DAGANG DALAM PERJANJIAN FRANCHISE COCOYO - Velliana Tanaya; Jessica Vincentia Marpaung; Audrea Dindya Djohan (Refleksi Hukum: Jurnal Ilmu Hukum, 2021)
Food and beverage franchise is one of the thriving businesses in Indonesia. In this industry, one of the most important elements is trade secrets. In practice, all franchises agreements have one or several articles governing the provisions regarding the granting of the trade secrets rights and violations of trade secrets. However, in reality, in the Cocoyo franchise agreement there are no clause regarding its trade secrets so it doesn’t provide legal protection for Cocoyo’s trade secrets. This research uses the normative legal research method in which this study will analyze the forms of legal protection against trade secrets in the Cocoyo franchise agreement. The agreement to protect and disclose Cocoyo’s trade secrets confidential was verbal. Although verbal, its trade secrets are still protected by law.